2016
DOI: 10.1002/aenm.201600014
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Degradation in Mesoporous Al2O3/CH3NH3PbI3‐xClx Perovskite Solar Cells: Kinetics and Mechanisms

Abstract: unexpectedly clean electronic properties of these semiconductors have led to the demonstration of proof-of-concept PV devices with an initial effi ciency that outperforms competing 'next-generation' technologies such as dye-sensitized, organic, and quantum dot solar cells, and even matches that of commercially deployed PV. [ 6 ] Other attractive characteristics of hybrid perovskites include the low embedded costs of materials processing and the ability to tune the properties of the semiconductor through change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
128
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 223 publications
(133 citation statements)
references
References 67 publications
(176 reference statements)
4
128
0
1
Order By: Relevance
“…Photocatalytic chemical reaction with absorption of ultraviolet (UV) light by TiO 2 is considered to induce achieved. [16,17] Haque and co-workers claimed that the degradation stems from the formation of reactive superoxide species in mediating halide vacancies in the perovskite materials. Even small amounts of oxygen can affect performances of PSCs since oxygen can easily react with halides.…”
Section: Perovskite Solar Cellsmentioning
confidence: 99%
“…Photocatalytic chemical reaction with absorption of ultraviolet (UV) light by TiO 2 is considered to induce achieved. [16,17] Haque and co-workers claimed that the degradation stems from the formation of reactive superoxide species in mediating halide vacancies in the perovskite materials. Even small amounts of oxygen can affect performances of PSCs since oxygen can easily react with halides.…”
Section: Perovskite Solar Cellsmentioning
confidence: 99%
“…[5,[51][52][53] In addition, the MAPbI 3 has also been shown to degrade more rapidly when exposed to light in an atmosphere containing oxygen, due to a chemical reaction between oxygen and MA + in the presence of electronic charge in the perovskite. [54] We have previously shown that formamidinium (FA)-based perovskites are much more thermally stable than methylammonium (MA)-based perovskite. [48,55] One problem with FAPbI 3 however is that it is not structurally stable in the black perovskite phase and undergoes a phase transition to a yellow phase at room temperature.…”
Section: Doi: 101002/adma201604186mentioning
confidence: 99%
“…Our perovskite cells composed of p and n-doped organic charge extraction layers are reasonably stable in air (which includes oxygen and moisture) and full spectrum sun light that includes the UV component, which indicates that the perovskite solar cells (this perovskite in this architecture) are not as sensitive to these environmental stressing components as previously thought. [18][19][20][21]49,54,64,65] 2. The n-doping of the C 60 appears to have a persistent beneficial effect over prolonged operation in air, indicating that the N-DPBI retains its doping function throughout the ageing test.…”
Section: Doi: 101002/adma201604186mentioning
confidence: 99%
“…6,[67][68][69][70][71] Ambient oxygen in combination with light can lead to direct photo-oxidation of the MAPbI 3 perovskite. 68,69 Those studies suggest that the accumulation of photogenerated electrons accelerates the oxygen-induced degradation of the perovskite absorber. Possible strategies for mitigating the oxygen assault on devices could therefore include effective barrier layers and oxygenimpermeable encapsulants, as well as efficient electron extraction layers.…”
mentioning
confidence: 99%